(untitled) (City Dental College Journal, 2012)
Objective: Aspects of an Artificial Mouth System (AMS) to model the caries process in bovine enamel biofilm induced white spot enamel lesions (WSEL) were analyzed. Methods: Square shaped and polished bovine enamel slabs were covered with modeling wax and 2.5 mm diameter window was prepared to expose enamel surface at the center of each slab. Artificial biofilms were grown inside an AMS on the slabs using freshly cultured S. mutans (MT8148) in suspended in phosphate buffered saline (PBS), heart infusion (HI) with 1% sucrose and PBS for 20, 30 and 40 hrs at 37°C. The severity of demineralization was quantified by Quantitative Light-induced Fluorescence (QLF, Inspektor, Netherlands). All experiments were repeated three times (n=5 for each group). Results: A circular WSEL could clearly be detected at the center of each slab by naked eyes, which was prominent after dehydration by mild air drying. QLF data showed that severity of demineralization occurred with the increase of time interval, after 40 hours both ?F (23+/-2.9) and ?Q (148.75+/- 26.78) were significantly more compared to ?F (10.14+/-2.3) and ?Q (47.63+/-30.67) of 20 hours. Conclusion: An advanced in vitro model of biolfilm induced WSEL was developed that showed promises to be useful in studying enamel demineralization. DOI: http://dx.doi.org/10.3329/cdcj.v9i1.11829 City Dental College Journal Vol.9(1) 2012 4-6